Systematics of disjunct northeastern Asian and northern north American Allium (Amaryllidaceae) - Choi, Hyeok Jae (2012)
This study was undertaken to better understand Allium infrageneric taxonomy, character evolution, species diversification, and patterns of radiation in disjunct species between the New and Old World using morphological and molecular data. Taxonomic sampling focused on northeastern Asian (mainly Korean and northeastern Chinese) and representative disjunct northern North American (Canadian) species. Pistil and seed testa morphology was investigated using light and scanning electron microscopy, respectively. These characters were useful to assess degree of relationship at different taxonomic levels in Allium. Phylogenetic studies included nrDNA ITS and cpDNA trnL-trnF sequence data analyzed using maximum parsimony approaches. Our molecular phylogeny recovers a similar topology to that published in recent studies and confirms three major evolutionary lines and patterns of radiation regarding the ancestors of subgenera Amerallium and Anguinum in the genus. The northeastern Asian and northern North American disjunction in this genus is inferred to be the result of multiple intercontinental migrations. Seed testa sculpture attributes in combination with seed shape provide key characters to distinguish Allium's major clades in the molecular phylogeny. The two types of ovarian processes, basal hood-like and apical crest-like in disjunct Old and New World species, respectively, are newly derived characters in each continent. Most infrageneric Allium groups are monophyletic, while subgenus Cepa is polyphyletic.